Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer:
r=6
Step-by-step explanation:
(r-(-3))/(2-(-1)) = (r+3)/3
r+3/3 = 3/1
cross-multiply:
r+3 = 9
r = 6
Check:
6-(-3)/2-(-1) should equal 3
9/3 = 3
checks out correctly
Answer:
r = 6
Step-by-step explanation:
Formula
m = (y2 - y1)/(x2 - x1)
Givens
x1 = - 1
x2 = 2
y1 = - 3
y2 = r
m = 3
Solution
3 = (r - -3) / (2 - - 1) Combine
3 = (r + 3) / 3 Multiply both sides by 3
9 = r + 3 Subtract 3 from both sides
6 = r + 3 - 3
6 = r
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.